(untitled) (Latakia University Journal -Engineering Sciences Series, 2019)
تأثير استخدام نواتج قص وصقل الغرانيت كفيلر في المونة الإسمنتية علي خيربك عماد فاضل نغم مفتي شهد قطاع البناء في سورية تطوراً كبيراً في الحقبة الأخيرة ، وأدى هذا التطور إلى ازدياد الطلب على مواد البناء بشكل كبير. وبسبب الظروف الراهنة زادت أسعار مواد البناء بشكل ملحوظ، ومن ناحية أخرى يعتبر التلوث البيئي أحد المشاكل التي تواجه العالم اليوم، لذلك تم التركيز في السنوات الأخيرة على مفهوم (البيتون الأخضر) أو ما يسمى Green Concreteو الذي يعتمد على استخدام النفايات الصناعية للحد من استهلاك الموارد الطبيعية وتوفير الطاقة وتقليل تلوث البيئة. ومع الزيادة في كمية النفايات الصناعية ولعدم وجود أماكن مخصصة للتخلص منها كان لابد من التفكير بإيجاد طريقة عملية للتخلص من الآثار السلبية التي تسببها هذه النفايات [3]. وتعتبر نواتج قص وصقل أحجار الغرانيت أحد هذه النفايات الصناعية التي يتم رميها بشكل عشوائي في الطبيعة . تم الحصول على الفيلر الغرانيتي من معمل الزين للرخام والغرانيت في مدينة اللاذقية. وتم تجفيفه وفصل برادة الحديد عن جزء منه لصنع عينات من المونة الإسمنتية بنسب استبدال مختلفة للرمل بالفيلر الغرانيتي ومن ثم إجراء الاختبارات اللازمة على العينات. بينت النتائج أن النسبة المثالية للاستبدال بين النسب المعتمدة كانت 15% حيث بلغت المقاومة على الضغط البسيط 281.25 Kg/cm² للفيلر المعالج و269 Kg/cm² للفيلر غير المعالج علما أن النسبة W/C المستخدمة لصب عينات المونة كانت مرتفعة نسبياً W/C= 0.65 لاعتبارات تخص قابلية التشغيل. The construction sector in Syria had a great development in the last era, which led to an increased demand for building materials. Due to the current conditions, the prices of building materials have increased significantly. On the other hand, environmental pollution is one of the most serious problems facing the world today. In recent years, the concept of Green Concrete, which is the use of industrial waste, has been focused on to reduce the consumption of natural resources, to save energy and to reduce the pollution of the environment. With the increase in the amount of industrial waste and the lack of disposal facilities, it was necessary to think about finding a practical way to eliminate the negative effects caused by these wastes.The products of cutting and polishing granite stones are one of these industrial wastes thrown randomly in nature. Filler Granite was obtained from Al-Zain Marble and Granite Factory in Lattakia. It was dried and separated iron filings from part of it for the manufacture of cement mortar samples with different replacement ratios of sand with granite filler and then testing the samples. The results showed that the optimum ratio of substitution between the approved ratios was 15% where the resistance was 281.25 Kg / cm² for treated granite filler and 269 Kg / cm² for untreated one. The w / c ratio used for casting mortar samples was relatively high w / c = 0.65 for considerations of workability